Judicial Decision Making: Intuitive and Rational Information Processing - Maceina, Tomas; Valickas, Gintautas (Teisė, 2019)
[full article and abstract in Lithuanian; abstract in English]The contributions of judges’ intuitive and rational information processing making decisions on criminal (robbery) cases were evaluated. Results are interpreted in the context of cognitive psychology and discussed in relation to the contemporary trends and future perspectives in the field of legal decsion-making.SummaryThe aim of the current study is to investigate the contributions of judges’ intuitive and rational information processing making decisions on criminal (robbery) cases. 98 judges working in various courts of Lithuania‘s general jurisdiction participated in this study. We asked participants to solve two vignettes. One vignette was designed to be compatible with intuitive information processing (i. e., anchor provided at the end of the vignette suggested a correct decision), while another counter-intuitive (i. e., anchor suggested incorrect decision). 51 judges were instructed to solve vignettes intuiti- vely under a limit time (intuitive group), 47 judges – rationally with no time constraints (rational group). Results of the current study revealed that intuitive group decided on higher sentences (i.e. was closer to an anchor), compared to rational group. Additonally, we found that judges’ in rational group rational information processing contributed to 53.19%, and intuitive information processing – to 8,51% of all decision-making process. Moreover, judges’ in intuitive group rational information processing contributed to 35.29%, and intuitive information processing – to 15,68% of all decision-making process. Results are interpreted in the context of cognitive psychology.
Keywords: intuitive information processing; rational information processing; dual processing; judicial decision making